GoBox - Ahmad Tarmizee, Aqib Syahir; Ahmad Khusairi, Ariff Hakimi; Mohamad Fauzi, Muhammad Zulhilmi; Zakaria, Nur Afiqah; Zuber, Nur Nadiah; Mohd Pauzi, Nur Farahah; Saidin, Amilia (Universiti Teknologi MARA, Kedah, 2023)
The ability of food rider delivery boxes to keep the temperature of the supplied food consistent is one of the biggest challenges they encounter. Several of the boxes lacked the right insulation, which resulted in the loss of heat or cold while the boxes were being delivered. Because of this, the meal may arrive at the doorstep of the customer in a less-than-desirable condition, which may have an impact on the customer's review of the dish's quality and overall satisfaction. This unique delivery box for food, which is called a GoBox, features two separate compartments that enable it to store both warm and cold food while preserving the perfect level of temperature control all the way through the delivery process. It is also strong enough to resist the obstacles of transportation and safeguard the food within from being damaged or spilled while it is being handled. By properly separating hot and cold items within a single delivery box, this innovation removes the need for separate packing or additional coolers, which in turn speeds up the delivery process and reduces the amount of waste that is wasted. The combination of a solar panel as a power source as well as modern tracking and monitoring technology not only raises the value of the product but also instills confidence in customers and makes it easier for companies to carry out their daily operations. This product was also available in two sizes; one was designed specifically for food delivery riders, and the other was a standard size that was convenient for all customers as a picnic bag for the public.